2003
DOI: 10.1123/jsep.25.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Dissatisfaction and Supplement Use among Male Intercollegiate Athletes

Abstract: Body image satisfaction was measured among college male athletes participating in track/cross-country, soccer, basketball, swimming, and lacrosse through the use of figure drawings varying in level of muscularity. All the athletes chose significantly different figure drawings to best represent their actual physique, ideal physique, and the physique they believed was most attractive to the opposite sex. For each sport, athletes’ actual physique was less muscular than both their ideal physique and the one they t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
7
22
0
2
Order By: Relevance
“…Student-athletes in high contact sports (i.e., football, rugby, basketball) reported significantly higher levels of drive for muscularity than student-athletes in both medium contact sports (i.e., soccer, volleyball, baseball) and those in low contact sports (i.e., cross country, tennis, track). This result is consistent with Raudenbush and Meyer's (2003) finding that contact sport participants required a more massive and muscular physique for functional purposes, and also indicated that their ideal body image was more muscular when compared to athletes in other sports. Furthermore, Ross and Shinew (2008) discussed sport appropriateness by noting that the female student-athletes in their study reported that sports that require bodily contact were more associated with masculinity.…”
Section: Drive For Muscularity Between Groupssupporting
confidence: 82%
See 2 more Smart Citations
“…Student-athletes in high contact sports (i.e., football, rugby, basketball) reported significantly higher levels of drive for muscularity than student-athletes in both medium contact sports (i.e., soccer, volleyball, baseball) and those in low contact sports (i.e., cross country, tennis, track). This result is consistent with Raudenbush and Meyer's (2003) finding that contact sport participants required a more massive and muscular physique for functional purposes, and also indicated that their ideal body image was more muscular when compared to athletes in other sports. Furthermore, Ross and Shinew (2008) discussed sport appropriateness by noting that the female student-athletes in their study reported that sports that require bodily contact were more associated with masculinity.…”
Section: Drive For Muscularity Between Groupssupporting
confidence: 82%
“…However, instead of female college students (only 17%) reporting the highest levels of external gratification reasons for being muscular (as hypothesized), statistically significantly more male student-athletes (41%) cited External Gratification as a reason they wanted to be muscular. Consistent with previous research suggesting that college men in the United States tend to overestimate the level of muscle mass that they think women find attractive in men (Lynch & Zellner, 1999;Raudenbush & Meyer, 2003), this finding may be related to external sociocultural pressures men face in conforming to standards of masculinity that emphasize attaining the ideal male body. Past research has examined ways that these standards have been conveyed by popular culture representations, with respondents often identifying the muscular body as the most masculine, and associating it with stereotypical masculine attributes such as self-confidence, strength, competence, aggressiveness, dominance, tenacity, and sexual potency (Biller & Liebman, 1971;Mishkind, Rodin, Silberstein, & Striegel-Moore, 1986).…”
Section: Reasons For Being Muscularsupporting
confidence: 79%
See 1 more Smart Citation
“…These relatively higher rates of pathogenic weight control behaviors are of concern because vomiting and laxative abuse are associated with severe medical complications, such as dehydration, esophageal tears, and cardiac arrhythmia (Rome & Ammerman, 2003), and may be precursors to the development of actual eating disorders. In addition, because we inquired only about these traditional forms of purging, we cannot rule out the possibility that the athletes were engaging in other problematic behaviors, such as ingesting muscle mass-weight gain supplements (e.g., Creatine), to control their weight and reshape their bodies (Raudenbush & Meyer, 2003). In future prevalence research with male athletes, it will be important (if allowed by coaches and athletic departments) to include a larger list of potential weight control behaviors, such as taking supplements or anabolic steroids, and to ask more detailed questions about the types of ex-ercise that male athletes are using to shape their bodies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In 2005, Field et al 3 reported that 12% of boys reported using supplements to improve appearance, muscle mass, or strength. More recently, in a 2012 study of 2793 adolescents at 20 urban middle and high schools in Minnesota, 34.7% of boys reported using protein supplements, 5.9% used steroids, and 10.5% used some other muscle-enhancing substance.…”
mentioning
confidence: 99%